Improving Students' Reading Comprehension through SQ3R Method: A Study at SMPN 2 Kampar Kiri - Pratama, Eggi; Raputri, Egi (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This study investigates the improvement of the SQ3R (Survey, Question, Read, Recite, Review) reading method in enhancing reading comprehension among third-year students at SMPN 2 Kampar Kiri. The research aims to identify the extent to which SQ3R improves reading comprehension. The study employs a quantitative approach, analyzing students' scores before and after implementing SQ3R. The findings of this study indicate that the SQ3R method significantly improved reading comprehension among third-year students at SMPN 2 Kampar Kiri. Students who used the method showed better understanding and retention of reading materials. The Survey and Question stages helped students focus on key information, while the Read, Recite, and Review stages enhanced recall.